The effects of bisphenols on the cardiovascular system ex vivo and in vivo. (February 2023) - Tvrdý, Václav; Dias, Patrícia; Nejmanová, Iveta; Carazo, Alejandro; Jirkovský, Eduard; Pourová, Jana; Fadraersada, Jaka; Moravcová, Monika; Peterlin Mašič, Lucija; Sollner Dolenc, Marija; Mladěnka, Přemysl
Abstract: The human population is regularly exposed to bisphenols. The first compound of this class, bisphenol A, is burdened by numerous reports of its potential toxicity and has been hence replaced by its analogues, so-called next generation bisphenols. Their widespread use has made them pervasive throughout the environment. These endocrine disrupting chemicals can affect the cardiovascular system, and hence the aim of this study was to test 14 bisphenols (A, AF, AP, B, BP, C, E, F, G, M, P, PH, S and Z), and compare their effects in vitro (human and rat cell lines), ex vivo (isolated rat aorta) and in vivo (Wistar Han rats, acutely or chronically exposed to low environmental and high toxic doses). The majority of the tested bisphenols relaxed rat aorta, but their potency varied markedly. The most potent compound, bisphenol AF, had an EC50 of 57 μM. The mechanism of action was likely based on the inhibition of calcium influx via L-type calcium channels. The cytotoxicity of bisphenols towards 4 human and rat cell lines (H9c2, A-10, MCF7/S0.5 and MCF7/182R-6) showed variable potencies ranging from units of micromolar to millimolar concentrations. Based on these data, an effect on arterial blood pressure and possible cardiotoxicity was expected. Contrarily, the in vivo acute effects of three doses (0.005, 0.05 and 2.5 mg/kg) of bisphenol AF and 3 other analogues (A, S and F) on the cardiovascular system were rather biologically negligible. The most potent bisphenol, AF, was also administered chronically at a dose of 2.5 mg/kg for 4 weeks to rats, but had no impact on arterial blood pressure. Our results showed that bisphenols can relax vascular smooth muscles, but the effective concentrations are too high to produce clear cardiovascular effects in relation to common biological exposure as was confirmed with the most potent bisphenol AF. Graphical abstract: Image 1 Highlights: 14 bisphenols were screened for their effect on rat aorta and cell cultures. Most bisphenols caused vasorelaxation likely via inhibition of L-type Ca 2+ channels. The most active bisphenol AF had mild effect on blood pressure when given i. v. Bisphenol AF was relatively toxic to rat cardiomyoblasts but not to other cells. No cardiac toxicity was found after chronic administration of bisphenol AF.